A review of the analysis of sandwich FGM structures - Garg, Aman; Belarbi, Mohamed-Ouejdi; Chalak, H.D.; Chakrabarti, Anupam (Composite structures, 2021)
Extensive literature on the analysis of sandwich FGM structures highlights the use of these structures as structural elements. In the present work, a detailed study has been carried out regarding the application of different methods and theories available in the literature for analyzing sandwich FGM structures under different loading conditions. The literature survey is carried out for sandwich FGM plates, beams, and shells. Effects of porosities, hygrothermal loadings, and structures resting on elastic foundations are also included during the review. Available manuscripts are categorized based on theories, material homogenization rules, and methods available for analysis in literature. The present review work will set a benchmark for future studies for carrying out further research in a similar direction.